Assessing the environmental sanitation improvement in urban communities in Vientiane City, LAO PDR - Somchaivang Dethoudom; Thammarat Koottatep; Annachhatre, Ajit P.; Perera, L.A.S. Ranjith; Government of Sweden (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
This study focused on the improvements of environmental sanitation system in three pilot communities; Ban Fay, Dongpalantha and Dongpalanthong villages in Vientiane City, Lao PDR. The study showed that the sanitation problems still exist in these communities, ranging from improper water supply, insufficient drainage system and improper solid waste generation. Due to the governmental policies, development initiatives and projects have been implemented in the Vientiane urban areas to improve the general perspectives of the city. These ongoing projects and organizations include VIUDP, VUISP, WMTM, IVUEP, VUDAA, VUCS and NPL. The responsibilities of each strategy and project have been described inside. Data from field investigations were conducted with respondents, head of villages, officer and some people who respond to the improvement of environmental sanitation system. It was found that 60%, 58% and 70% of households are using cesspools; about 14%, 6% and 12% of respondents were unsatisfactory with sanitary condition in Dongpalantha, Ban Fay and Dongpalalnthong villages, respectively. There are 34%, 30% and 36% of people who want to improve storm water drainage systems, around 92%, 88% and 90% of responds who agree to pay for improvement of greywater disposal. The generation of wastewater and sewage is also posed as the major environmental issues due to improper system to collect and treating the wastewater. The current situation of these pilot communities' shows that Ban Fay and Dongpalanthong use on-site sanitation system, cesspool covering about 58%, 60% and 70% of the total wastewater production. The rest are latrines and toilets. The wastewater and water quality analysis of the study areas were also included. The results of the analysis on wastewater characteristic in Dongpalantha, Ban Fay and Dongpalanthong villages respectively, TSS was 34, 34 and 82 mg/l; TSD was 241, 282 and 319; NH3-N was 21, 23 and 23 mg/l; TKN was 24 and 27 mg/l; Faecal coliform was 19X10, 16x10 and 15x10 MPN/100 mL; COD was 116,97 and 121 mg/1; and BOD 56, 54 and 61 mg/l. In order to improve the environmental sanitation system in the Vientiane urban areas, Material Flux Analysis (MFA) has been proposed by comparing three scenarios: (i) constricting of the composting site and reuse of organic matter in the agriculture land; (ii) establish the new septic tanks for all households in Ban Fay, Dongpalantha and Donapalanthong villages where there is no on-site sanitation system; (iii) build up the constructed wetland in Dongpalantha village (near Nongchanh pond) to treat the wastewater and sewage from the households. The results of MFA analysis indicate that, these villages are discharging large amount of N into the environment from solid waste generation and human excreta. Dongpalantha, Ban Fay and Dongpalanthong villages generate about 13; 13 and 13 g/capita'day, respectively. Dongpalantha village generates about 77% of total N input while Ban Fay and Dongpalanthong villages generate almost 1000 of total N input. After proposing the new scenarios improving environmental sanitation, N output can he reduced from 18% to 99.8% in these three villages.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 2006
Keywords: Sanitation -- Laos -- Vientiane -- Environmental aspects; Community development, Urban -- Laos -- Vientiane -- Environmental aspects